Toxin GhoT of the GhoT/GhoS toxin/antitoxin system damages the cell membrane to reduce adenosine triphosphate and to reduce growth under stress. (21st January 2014) - Cheng, Hsin‐Yao; Soo, Valerie W. C.; Islam, Sabina; McAnulty, Michael J.; Benedik, Michael J.; Wood, Thomas K.
Summary Toxin/antitoxin (TA) systems perhaps enable cells to reduce their metabolism to weather environmental challenges although there is little evidence to support this hypothesis. Escherichia coli GhoT/GhoS is a TA system in which toxin GhoT expression is reduced by cleavage of its messenger RNA (mRNA) by antitoxin GhoS, and TA system MqsR/MqsA controls GhoT/GhoS through differential mRNA decay. However, the physiological role of GhoT has not been determined. We show here through transmission electron microscopy, confocal microscopy and fluorescent stains that GhoT reduces metabolism by damaging the membrane and that toxin MqsR (a 5′‐GCU‐specific endoribonuclease) causes membrane damage in a GhoT‐dependent manner. This membrane damage results in reduced cellular levels of ATP and the disruption of proton motive force (PMF). Normally, GhoT is localized to the pole and does not cause cell lysis under physiological conditions. Introduction of an F38R substitution results in loss of GhoT toxicity, ghost cell production and membrane damage while retaining the pole localization. Also, deletion of ghoST or ghoT results in significantly greater initial growth in the presence of antimicrobials. Collectively, these results demonstrate that GhoT reduces metabolism by reducing ATP and PMF and that this reduction in metabolism is important for growth with various antimicrobials.